Experimental and theoretical studies on a double-pass C-band bismuth-based erbium-doped fiber amplifier - Harun, Sulaiman Wadi; Parvizi, R.; Cheng, X.S.; Parvizi, A.; Emami, S.D.; Arof, Hamzah; Ahmad, Harith (Elsevier, 2010)
Performance of a Bismuth-based Erbium-doped fiber amplifier is experimentally and theoretically investigated using 1480 nm pumping with double-pass scheme. In the theoretical analysis, the rate and power propagation equations are solved to examine the optimum length for the C-band operation as well as the gain and noise figure characteristics. The calculated small signal gain is 38 dB with gain variation of less than 3 dB. The measured gain is 4 dB lower due to spurious reflections which were ignored in the theoretical analysis. At input signal power of 0 dBm, a gain of 14.5 dB is obtained experimentally with gain variation of less than 1 dB within the wavelength region from 1530 to 1565 nm. The noise figure is less than 12 dB within this region. (C) 2009 Elsevier Ltd. All rights reserved.